The Impact of Surplus Distribution on the Risk Exposure of With Profit Life Insurance Policies Including Interest Rate Guarantees - Alexander Kling; Andreas Richter; Jochen Ruß (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2006)
This paper analyzes the numerical impact of different surplus distribution mechanisms on the risk exposure of a life insurance company selling with profit life insurance policies with a cliquet-style interest rate guarantee. Three representative companies are considered, each using a different type of surplus distribution: A mechanism, where the guaranteed interest rate also applies to surplus that has been credited in the past, a slightly less restrictive type in which a guaranteed rate of interest of 0% applies to past surplus, and a third mechanism that allows for the company to use former surplus in order to compensate for underperformance in “bad” years. Our study demonstrates that regulators should be very careful in deciding which design of a distribution mechanism is to be enforced. Within our model framework, a distribution mechanism of the third type yields preferable results with respect to the considered risk measure. In particular, throughout the analysis, our representative company 3 faces ceteris paribus a significantly lower shortfall risk than the other two companies. Requiring “strong” guarantees puts companies at a significant competitive disad¬vantage relative to insurers which are subject to regulation that only requires the third type of surplus distribution mechanism. This is particularly true, if annual minimum participation in the insurer's investment returns is mandatory for long term contracts.
urn:nbn:de:bvb:19-epub-1220-8
Keywords: G18; G22; 650; life insurance; interest guarantees; surplus distribution